Performance evaluation of phase changing material based first generation liquid chilling unit - Sharma, Amandeep; Kaur, Kulwinder; Chhina, Ravinder Singh (Indian Journal of Dairy Science, 2016)
Cooling of milk immediately after milking is necessary to preserve the quality of milk and to prevent an excessive increase in number of bacteria. In the prevailing methods of milk handling, raw milk is collected in cans and transported to chilling centre without any primary chilling at root level. Lack of raw milk chilling facilities or bulk milk chillers at village level results in spoilage of the milk. Handling and transportation methods of milk to the chilling centres are also very crude. Keeping in view the need of primary chilling as well as proper transportation, a phase changing material (PCM) based first generation liquid chilling unit was designed by Guru Angad Dev Veterinary and Animal Sciences University, Punjab. The performance of 40 litres of batch type prototype was evaluated running preliminary trials on water considering different process conditions: 1) portion wise addition of product, 2) addition of product immediately after phase change and 3) addition of product after overnight of phase change. The optimized condition from the above trials was evaluated in terms of cooling capacity and final experiments were run on milk. The experiments were carried out with and without agitation of the product so as to study their effect on rate of cooling. The performance evaluation has shown that the milk can be chilled to 4oC within two hours by treatment 2 (without agitation) and the temperature can be maintained for more than 12 hours.Â